2022
DOI: 10.1109/jtehm.2021.3133485
|View full text |Cite
|
Sign up to set email alerts
|

The Compressiometer: Toward a New Skin Tensiometer for Research and Surgical Planning

Abstract: After surgery, around 35% of patients experience problems of excessive scarring, causing disfiguring and impaired function. An incision placed in the wrong direction causes unnecessary skin tension on the wound, resulting in increased collagen disposition and potentially hypertrophic scars. Currently, skin tension lines are used for incision planning. However, these lines are not universal and are a static representation of the skin tension that is in fact under influence of muscle action. By designing a new s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…The preferred direction changes in different body postures were not always consistent with current recommendations such as Langer's Lines. These results correspond with the data from a previous pilot study that also indicated a relationship between body posture and measured reaction force 12 . The prevention of pathological scar tissue formation after (skin) surgery remains challenging.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The preferred direction changes in different body postures were not always consistent with current recommendations such as Langer's Lines. These results correspond with the data from a previous pilot study that also indicated a relationship between body posture and measured reaction force 12 . The prevention of pathological scar tissue formation after (skin) surgery remains challenging.…”
Section: Discussionsupporting
confidence: 90%
“…This study used a novel compressiometer (Fig. 1 ) recently developed and validated by the authors 12 . The device was used to determine the reaction force of the skin by determining the displacement of two fixed points on the skin under unidirectional loading.…”
Section: Methodsmentioning
confidence: 99%
“…One of the most important causes of pathological healing, such as hypertrophic scars, is incorrect incision planning. An incision placed in the direction perpendicular to Langer’s lines causes unnecessary tension on the skin, pushing the wound edges apart [ 18 ], substantiating the last criterion mentioned. Only women who consented to be contacted were evaluated by resorting to other instruments, from which those who presented diastasis of the rectus abdominis greater than two fingers of the subject, types V and VI phototypes (Fitzpatrick Scale), obesity (Body Mass Index (BMI) greater than 29.99 kg/m 2 ), and were undergoing menopause, were excluded.…”
Section: Methodsmentioning
confidence: 86%
“…Ziel (i) Report über die quantitative Messung der Wundspannung bei experimentellen Hautwunden unter Verwendung eines neu entwickelten Wundtensiometers und (ii) Entwicklung Introduction Halsted's 7 principles of surgery have been established for over 120 years [1], but objective data on wound tension are limited. Subjective assessment of wound tension by experienced surgeons remains the gold standard in small animal surgery, as there are no established methods for objective quantification or reference values for wound tension to guide the surgeon's decision whether to close the wound primarily without any tension-relieving procedures [2]. The detrimental impact of high wound tension on wound healing has led to the development of a variety of tension relieving techniques [3].…”
Section: Zusammenfassungmentioning
confidence: 99%